Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

If (1+ x - 2x^2)^6 = 1+ a1x + a2x^2 +.........+ a(12)x^12, then prove that a2+a4+a6+........+a12 = 31. Thank u

If (1+ x - 2x^2)^6 = 1+ a1x + a2x^2 +.........+ a(12)x^12, then prove that a2+a4+a6+........+a12 = 31.

Thank u 

Grade:11

2 Answers

Aravind Kashyap
30 Points
8 years ago

TRY THIS...FIRST KEEP X= THEN X= OMEGA AND THEN X= OMEGA SQUARE. AND ADD ALL THE THREE EQUATIONS....U WILL GET TAHT RESULT...HOPE U GOT MY POINT..THANKU

orange panda
4 Points
8 years ago

put x=1,-1,0 and then add them.

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free